How do taxable income responses to marginal tax rates differ by sex, marital status and age? Evidence from Spanish dual income tax - Carlos Díaz-Caro; Jorge Onrubia Fernández (Kiel Institute for the World Economy (IfW), 2018)
The aim of this paper is to analyze how Spanish taxpayers have responded to the introduction of the dual personal income tax model in 2007. The authors estimate the elasticity of taxable income (ETI) with respect to the marginal net tax rate for different groups of taxpayers by sex, marital status and age, separating the substitution effect from the income effect. For the empirical analysis, they use microdata from the Spanish personal income tax return panel disseminated by the Spanish Institute of Fiscal Studies. The main results show that the 2007 tax reform resulted in a range of elasticity values from 0.41 to 0.43, while the estimated income effect yields a negative value of -0.18. The results for the different taxpayer groups are as follows: the removal of retired people from the sample significantly reduces the ETI; elasticity is higher for women than for men; single people have a considerably higher elasticity than married taxpayers; and the ETI decreases with age. Additionally, the authors find that the marginal cost of public funds increased after the reform, and the top marginal tax rate is above optimal.
Keywords: H21; H24; H31; 330; elasticity of taxable income (ETI); tax reforms; dual income tax; marginal cost of public funds; optimal tax rates